Prevalence and predictors of tobacco smoking in veterans and service members following traumatic brain injury rehabilitation: a VA TBIMS study. (3rd July 2018) - Silva, Marc A.; Belanger, Heather G.; Dams-O'Connor, Kristen; Tang, Xinyu; McKenzie-Hartman, Tamara; Nakase-Richardson, Risa
ABSTRACT: Objective : To identify prevalence and predictors of tobacco smoking among veterans and military service members (V/SM) with traumatic brain injury (TBI) admitted for rehabilitation. Methods : Participants were drawn from the VA TBI Model Systems multicentre longitudinal research study. Tobacco smoking was assessed both preinjury and at 1- or 2-year post-TBI follow-up for 336 participants. Results : Smoking prevalence was 32% preinjury and 28% at follow-up. Most participants had a stable smoking pattern but 12% of preinjury non-smokers became smokers at follow-up. Preinjury smoking was the strongest predictor of post-TBI smoking. Higher cognitive function also predicted smoking at follow-up. In univariate analyses, smoking was predicted by lower education, preinjury mental health (MH) history, selected TBI severity metrics, and higher functional status at rehabilitation hospital discharge (Disability Rating Scale [DRS] and motor subscale of the Functional Independence Measure [FIM]). Conclusion : Study findings may help clinicians and administrators recognize who is at high risk for smoking following TBI, to plan for in-hospital and postdischarge screening and interventions.